Coenzyme A‐Conjugated Cinnamic Acids – Enzymatic Synthesis of a CoA‐Ester Library and Application in Biocatalytic Cascades to Vanillin Derivatives. Issue 23 (18th November 2019) - Dippe, Martin; Bauer, Anne‐Katrin; Porzel, Andrea; Funke, Evelyn; Müller, Anna O.; Schmidt, Jürgen; Beier, Maria; Wessjohann, Ludger A.
Abstract: We present a bioorthogonal method for the ligation of coenzyme A (CoA) with cinnamic acids. The reaction, which is the initial step in the biosynthesis of a multitude of bioactive secondary metabolites, is catalyzed by a promiscuous plant ligase and yields CoA conjugates with different functionalization in high purity and without formation of by‐products. Its applicability in biosynthetic cascades is shown for the direct transformation of cinnamic acids into natural benzaldehydes (like vanillin) or artificial derivatives (e. g. ethylvanillin). Abstract :